Perspectives on eDNA monitoring in Alpine waters - Kurmayer, Rainer (knjige, 2021)
Exciting results, perspectives, guidelines and policy recommendations for eDNA monitoring and more...
Keywords: alpske dežele; biomonitoring; Celinske vode; Ekološko stanje; elektronske knjige; interpretacija; okoljska DNA; rezultati; Srednja Evropa; vode; Vrednotenje